Peningkatan Kompetensi Digital Marketing Melalui Pelatihan Canva Bagi Mahasiswa Ilmu Komunikasi - Mursalin, M; Ali, Muhammad (Asskruie: Jurnal Pengabdian Kepada Masyarakat, 2024)
This community service aims to improve digital marketing competencies of communication science students which are carried out through Canva training. The background is the gap between industrial demands and graduate skills in the digital age, especially in the aspect of visual communication for digital marketing. The implementation method includes intensive training in the use of canva, including the basic theory of visual design and direct practice of making digital marketing content. The expected result is an increase in the ability of students to create interesting and effective visual content for digital marketing strategies. This activity also aims to increase awareness of the importance of this skill in the communication science curriculum. Follow -up includes evaluating the impact of training on academic performance and student career projections, as well as the potential integration of similar training into the regular curriculum. Through this initiative, it is expected to strengthen the relevance of communication education to industrial needs in the digital age.